2019
DOI: 10.2106/jbjs.19.00858
|View full text |Cite
|
Sign up to set email alerts
|

Primary Arthroscopic Stabilization for a First-Time Anterior Dislocation of the Shoulder

Abstract: Background: The aim of this study was to evaluate the long-term efficacy of arthroscopic Bankart repair (ABR). Methods: Eighty-eight patients with an age of ≤35 years who had sustained a primary anterior glenohumeral dislocation were enrolled in a single-center, double-blinded clinical trial. Subjects were randomized to receive either an arthroscopic washout (AWO) or ABR. Participants were reassessed after a minimum of 10 years postoperatively. Data reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Moore et al 21 34 DS 1 (3) 2 (6) (9) Yapp et al 62 32 DS 4 (12) 3 (9) 7 (21) Rhee et al 63 48 DS requiring revision surgery 1 (2) 3 (6) (2) Oh et al 64 120 Dislocation or positive apprehension 12 (10) 14 (12)…”
Section: Critical Appraisal and Definition Of Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…Moore et al 21 34 DS 1 (3) 2 (6) (9) Yapp et al 62 32 DS 4 (12) 3 (9) 7 (21) Rhee et al 63 48 DS requiring revision surgery 1 (2) 3 (6) (2) Oh et al 64 120 Dislocation or positive apprehension 12 (10) 14 (12)…”
Section: Critical Appraisal and Definition Of Recurrencementioning
confidence: 99%
“…Definition of dislocation Dislocation needing reduction (by medical professional or third party) 12,16,19,26,31,33,34,37,57,58,68,70,[72][73][74]87,91,102 Objective documentation of a dislocation either radiologically or clinically 24,32,59,62,71,75,92 Increased translation of the humerus relative to the glenoid to the point of complete separation of articular surfaces 96 More than 1 episode of instability which needed manual reduction by other people 97…”
Section: Table 3 Definitions Of Dislocation and Subluxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in contact sports, such as rugby, football, basketball, and hockey increases the risk of recurrence. Operative treatment may be preferred in these patients and in younger patients (<40 years) to reduce recurrence 3637. A systematic review (17 studies, 642 patients) evaluating return to sport in athletes aged ≤18 years showed that 41% return to sport (return to pre-injury level or higher) following physical therapy and 95% return to sport following operative treatment 38…”
Section: What Does Long Term Management Involve?mentioning
confidence: 99%
“…Arthroscopic treatment has become the gold standard therapy for symptomatic anterior shoulder instability, offering good clinical results and high return-tosport rates [14,25]. One remaining area of concern is the high recurrence rate of up to 25% that was found to be associated with younger age and the number of anchors used for the fixation of the capsulolabral structures [1,3,17,19,22].…”
Section: Introductionmentioning
confidence: 99%